The Complex Relationship between Sunni Scholars and Sufi Mystics in the Middle Ages: A Case Study of al-‛Izz ibn ‛Abd al-Salām - Abboud, Saleh (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This article interrogates the intricate nexus between Sunni jurisprudence and Sufi mysticism during the Ayyubid and early Mamluk eras, utilizing the preeminent jurist al-ʿIzz ibn ʿAbd al-Salām (d. 660 AH/1262 CE) as a focal point. The study addresses a core historiographical problem: the presence of discordant medieval narratives regarding al-ʿIzz’s formal affiliation with Sufi orders and his jurisprudential stance on Sufi praxis. To resolve this, the research pursues two pivotal questions: To what extent was al-ʿIzz genuinely integrated into Sufi circles, and how did his legal framework delineate the boundaries of permissible Sufi conduct and institutionalization? Employing a qualitative inductive methodology, the research systematically triangulates evidence from al-ʿIzz’s authenticated legal and ethical treatises (primary corpus) against diverse medieval biographical and hagiographical sources (secondary corpus/Ṭabaqāt). This analytical framework facilitates a critical distinction between established doctrinal positions and retroactive hagiographical attributions. The findings demonstrate that while al-ʿIzz maintained a profound intellectual rapport with orthodox Sufi luminaries—notably al-Shādhilī—and embraced the ethical-ascetic dimensions of Taṣawwuf, his verified writings articulate a rigorously selective endorsement. As a reformist jurist, he sanctioned Sufism only insofar as it remained tethered to Shari'ah-centric orthodoxy, while vehemently repudiating ritualistic innovations (Bidʿah) such as Samāʿ (ecstatic sessions). Consequently, the significance of this study lies in redefining al-ʿIzz not as a formal Sufi initiate, but as a paradigmatic “juristic gatekeeper.” These conclusions contribute to the broader discourse on medieval Islamic intellectual history by elucidating the mechanisms of scholarly policing of spiritual boundaries and the complexities of manuscript-based historical reconstruction.